THE RELATIONSHIP BETWEEN RELIGION AND SCIENCE IN POLICIES ON EARLY MARRIAGE IN INDONESIA: The Perspective Of Ian G Barbour - Soleh, Achmad Khudori; Hakim, M Aunul; Taufiqurrahman, Muh. (Universitas Islam Madura, 2025)
The relationship between religion and science is a complex issue that often arises. In the context of early marriage, religion and science have different paradigms in responding to the age of marriage. The relationship between religion and science from Barbour's perspective is considered important to study in understanding and addressing the dynamics of early marriage age policies in Indonesia. This study aims to explore the relationship between religion and science in formulating marriage age policies in Indonesia. The method used in this study is library research. The results of this study explain that, (1) Ian G. Barbour categorizes the relationship between religion and science into four typologies: conflict, independence, dialogue, and integration. (2) Although early marriage practices still occur due to social, economic, and cultural factors, integrative efforts between religious views and scientific data (reproductive health, child psychology) show that the dialogue and integration approaches are effective bridges between religious values and modern scientific findings. (3) In the context of marriage age policies in Indonesia, the relationship between religion and science tends to move from conflict toward a model of dialogue and even integration. This is reflected in the alignment between state policy, through the revision of Law No. 1 of 1974 into Law No. 16 of 2019, and the MUI fatwa supporting marriage age restrictions for the greater good.